Membangun Kemandirian Ekonomi Desa Melalui Kewirausahaan Sosial Di Desa Pancakarya Kecamatan Tempuran Karawang - Susanto, Heri; Sofyan, Ade; Novitasari, Intan (LPPM Universitas Harapan Bangsa Purwokerto, 2025)
The community service program through social entrepreneurship in Pancakarya Village aims to increase community knowledge and skills in utilizing local potential as an economic source. This activity is implemented through two main stages: (1) Socialization and Social Entrepreneurship Training with discussion, brainstorming, and case study methods to explore local potential, and (2) Marketing Network Strengthening Training to improve product marketing capabilities. The evaluation results showed a significant increase in participants' understanding by 30% based on the comparison of pre-test and post-test. Some participants have initiated new businesses, such as the development of organic agricultural products and handicrafts that are marketed online. The training also succeeded in building a collaborative network among participants to share marketing strategies. Regular monitoring and evaluation of the participants' business development will be carried out in the next stage of the mentoring program to help develop their businesses and assist in joint marketing programs to help participants market their products more effectively.